The Relationship Between Early Marriage And Anc Compliance And Lbw Incidence In Gunungrejo Village Singosari District - Setiasih Agustina; Rosyidah Alfitri (Jurnal Maternitas Kebidanan, 2026)
Early marriage is often followed by pregnancy at a young age who biologically have not reached optimal reproductive maturity, thus increasing the risk of complications during pregnancy, childbirth, and the postpartum period. The purpose of this study was to determine the relationship between early marriage and ANC compliance and the incidence of LBW in Gunungrejo Village, Singosari District, Malang Regency. The type of research used was descriptive analytic using a cross-sectional study design. The number of samples used was 20 taken by accidental sampling. Data analysis used chi-square test analysis. The results showed that there was a relationship between early marriage and ANC compliance P-value = 0.002 <0.05. And there was no relationship between early marriage and the incidence of LBW, P-value = 0.2 > 0.05. The conclusion is that there is a relationship between early marriage and ANC compliance but there is no relationship between early marriage and the incidence of LBW. Suggestions from this study are that early marriage can be prevented so that mothers and the generation born are healthy and prosperous.